MORE THAN JUST SMOKE AND LIGHTS: THE ARCHITECTURE OF CONCERT STAGE DESIGN - Dingman, Leah (University of Waterloo, 2023)
Live music creates an environment that allows your mind to go silent, where all your senses are stimulated in perfect harmony. It’s a heightened sense of reality, a place to escape and be consumed in something that feels like your bones are being hugged. Architecture is what is used to make these ethereal moments a reality. Architecture plays a pivotal role in amplifying the overall experience for the audience and performer by creating an immersive spectacle, yet architects have frequently been left out of the conversation of concert stage design, which has led to underdeveloped immersive concerts. Concert design has now become an oversaturated field and an architect’s contributions have not yet been fully understood. By understanding how the skills of an architect can be utilized in concert design, elements such as space, scale, sightlines, functionality and aesthetics can transform arenas into engaging environments, and transcend the audience into new realms. To understand the role of an architect within this field of design, research was conducted to understand the last 100 years of performance history, the core materials and effects used in sets, the different types of stages, the expectation of the spectacle, and design logistics. With this research, I seek to contribute to the broader discourse on the fusion of architecture, live music, and emotion, by analyzing how different architectural elements such as stage shape and scale can evoke different emotions for the audience. The findings of this research are tested through the comprehensive design of three stages, each of which aims to emphasize specific emotional responses, and use different architectural elements that transform space to address said emotions. The stages are designed respectively around three songs composed and performed by the R & B artist Labrinth. Labrinth is a highly dynamic and versatile artist with a discography of music that includes a range of styles, tempos and emotions. Additionally, Labrinth has yet to go on a full arena scaled tour, allowing for an uninfluenced imagining of his performances. The first stage is designed for his song “Jealous”. “Jealous” is a slow and dreamy composition, therefore the corresponding stage uses lightweight architectural elements, including hanging, interactive fabrics that evoke an ethereal environment. The second stage is designed for the song “When I R.I.P.” which is a more rhythmic and high tempo song, so the corresponding stage design transitions into a profile stage with a grounded, heavy base and overhanging roof. This stage typology creates an intense and edgy environment due to its invasive protrusion into the audience, and added stark materiality. The final stage is for Labrinth’s song “Sexy MF” which is an upbeat, high energy song that inspires dancing and togetherness. The resulting stage design utilizes a large roof structure that encapsulates both Labrinth and the audience, effectively creating an interconnection within the space. These architectural contributions will envision new possibilities that push the boundaries of concert stage design past just smoke and lights, revolutionizing the way we experience live performances.